Functional, UV-curable coating for the capture of circulating tumor cells. (27th March 2019) - Song, Wanyun; Li, Xinyi; Zhao, Yuquan; Liu, Chaoying; Xu, Junying; Wang, Huiyu; Zhang, Tao
Abstract : Facile UV-curable coating method to immobilize antibodies for the development of medical devices in order to capture the circulating tumor cells. Abstract : The capture of circulating tumor cells (CTCs) plays a crucial role in the early diagnosis, personalized treatment and postoperative evaluation of malignant tumors. In this study, UV-curable coating technology was combined with antibody immobilization to enable CTC captures on poly(methyl methacrylate) (PMMA) substrates. Controlled amounts of carboxyl groups and polyethylene glycol (PEG) segments were introduced into the coating formulation to facilitate immobilization of antibodies and block non-specific protein adsorption, respectively. Then, anti-EpCAM antibodies were immobilized on functionalized, coated PMMA substrates by EDC/NHS chemistry. Multiple physical, chemical and biological properties were investigated, including hydrophilicity, protein adsorption, platelet adhesion and anticoagulant properties. Thereafter, optimized coatings were applied on the inner wall of PMMA tubes, followed by immobilization of anti-EpCAM antibodies. After perfusion of the tubes with whole blood, enriched with SGC7901 gastric cancer cells that overexpress EpCAM antigens, rapid and efficient capture of the tumor cells was observed. These results provide a basis for further development of devices for the selective capture and enrichment of CTCs, using small blood volumes.